Portable Dental Chairs in Supporting Dental Health Services in the Field Reviewed from the Aspect of Examination Quality - Rindharso, Rahmaisynta Putri; Kusasi, Edy; Sofian, Rizki (Center of Excellent (Pusat Unggulan Iptek), 2025)
Background: The government and health institutions are trying to improve access to dental services through field activities, but are hampered by facilities, especially dental chairs. Portable dental chairs are considered effective because they increase patient comfort, support ergonomic working positions for operators, and maintain examination quality. This study analyzes the effectiveness of their use through evaluation of examination quality aspects, with data obtained from surveys, observations, and questionnaires on dental and oral therapists in field services. Methods: This study used a mixed method (descriptive and analytical) with a Research and Development (R&D) design aimed at developing and testing product effectiveness. The study participants were 30 dental therapists from all community health centers in Banjarbaru City, South Kalimantan, with a data collection duration of one month. Results: The results of the effectiveness test of the use of the Portable Dental Chair model in dental health services in the field reviewed from the aspect of examination quality obtained a value of 0.000 (p<0.05). Conclusion: The portable dental chair model effectively supports the quality of examinations in dental health services in the field.